Business Digital Role for Sustainable Traditional Business: A Case Adapting Innovation in SMEs Batu Malang - Farani, Dinesh Basti; Puspitasari, Dyah Ayu Kunthi; Taali, Muhammad; Amri, Lala Hucadinota Ainul; Amri, Whan Augustin Ainul (International Journal of Social and Management Studies, 2024)
Currently, the role of digital business has become an important part and even a major factor in maintaining business continuity. Businesses that cannot adapt to this trend are at risk of stagnation or even decline, including traditional businesses. Traditional business is a model that relies on old methods, such as direct consumer sales. This study uses a qualitative method with a data triangulation approach to evaluate the extent to which MSMEs in Batu Malang adapt to digital business innovations to maintain their business continuity. The results of the study indicate that MSMEs must immediately make improvements to support their businesses. One way is to utilize digital business, such as marketing through online platforms such as social media. In addition, monitoring social media related to trends and the needs of consumers and tourists is also needed so that businesses can meet customer desires. Other aspects are innovation, digitalization, and ease in the payment process. This finding is also supported by the fact that the trend of cashless transactions has become a new habit.